The objective and the prospects of creating certified reference materials of fire protection substances and materials - M. P. Dubinin; N. V. Afanasiev; A. L. Pyatov (Стандартные образцы)
The article describes the state of things in the field of production and use of fire protection materials. The need to develop certified reference materials of fire protection materials is justified.